Emergency, future safeguards and the habeas corpus case - Seervai ,H.M. (Bombay, 1978)
On June 25, 1975, the President of India proclaimed an emergency on the sole advice of Prime Minister Indira Gandhi, for she had no authority from her Council of Ministers to tender such advice. With every week that passed, the dark pall of tyranny seemed to descend inexorably over India. In this encircling gloom there was one kindly light. The High Courts stood firm in upholding the Rule of Law. Nine High Courts held, on petitions for writs of habeas corpus, that al though the Presidential Order under Article 359 of our Con stitution barred the enforcement of certain fundamental rights, the petitions were maintainable if the orders of detention were not authorised by law or were contrary to law or were mala fide. The High Courts thus upheld the vital principle that though the emergency barred the enforcement of certain fundamental rights it did not abrogate the rule of law, or the obligation to obey the law. However, on April 28, 1976, in A.D.M. Jabalpur v. Shivkant Shukla (the "Habeas Corpus Case") Chief Justice Ray, and Justices Beg, Chandrachud and Bhagwati reversed the nine High Courts Justice Khanna - dissenting. The majority held, in effect, if not in intent, that as to life and personal liberty, all laws in India were abrogated during the emergency. Coming at the darkest period in the history of independent India, it made the darkness complete. The disastrous consequences of this judgment and the grave public mischief it produced were known to a few and were suspected by many more. However, a "draconian" censor ship, backed by preventive detention without reason assigned and without redress-concealed from the public gaze the magnitude of the mischief which the Supreme Court judgement had in fact produced.
Keywords: Emergency